Diagnosis and Management of Pseudo-Pericarditis due to Theileriosis in Cattle - Prajapati, Ankit S.; M. Chauhan, Prakash (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Theileriosis is one of the common economic concerns in cattle, and normally hyalomma ticks transmit it. The estimated economic loss due to tropical theileriosis in India is INR 8,426.7 crore (Narladkar, 2018). Cattle have been thought to be susceptible animals in older days; however, the disease is also prevalent in buffalo, sheep and goats. Pale mucus membrane, enlarged lymph nodes, progressive weight loss and high fever are the routinely observed clinical signs in cattle (Patel et al., 2022). Blood smear examination and molecular confirmation are widely adopted for diagnosis. In large ruminants, various unusual clinical signs, including exophthalmos and pseudo-pericarditis, have been reported for a long time (Prajapati et al., 2019). Pseudo-pericarditis refers to jugular engorgement and edema of the brisket and ventral abdominal wall resulting from pressure at the cranial and caudal vena cava, which return blood to the heart (Radostits et al., 2000). The reported condition must be differentiated from true pericarditis for proper therapeutic management. In this case, the diagnosis of pseudopericarditis has been described along with management in cattle Ca s e Hi s to ry a n d Ob s e r vat i o n An eight-year-old crossbred cow with a history of brisket edema for the last 3 months, laboured breathing, enlarged pre-scapular lymph node and blackish bloody diarrhoea was brought for treatment at Veterinary Clinical Complex, Deesa, Gujarat India (Fig. 1A). Primary examination revealed a pale conjunctival mucus membrane and 103ºF rectal temperature. Ferroscopy carried out to rule out the presence of a foreign body was found to be negative. A small amount of faeces was collected to evaluate the parasitic load in the body, and no ova of any parasites were found. 2 mL of blood was collected for further investigation. The complete blood count revealed white blood cells 20.34 x 103/µL,, red blood cells 1.71 x 106/μL, haemoglobin 2.2 g/dL, packed cell volume 7.05 %, platelets 360 x 103/μL, lymphocyte 27%, monocyte 1 % and neutrophils 72 %. The field-stained blood smear examination revealed Koch’s blue bodies in lymphocytes (Fig. 1B). Meanwhile, an ultrasonographic evaluation of the thorax was carried out using a 2-5 MHz convex probe, and an accumulation of fluid around the heart was recorded (Fig. 1C). Further, PCR done for molecular confirmation of T. annulata infection using forward primer CCAGGACCACCCTCAAGTTC and reverse
Keywords: estimated economic; tropical theileriosis; pseudopericarditis; ventral abdominal